Do styles of emotion dysregulation differentiate adolescents engaging in non-suicidal self-injury from those attempting suicide?. (September 2020) - Kim, Kerri L.; Galione, Janine; Schettini, Elana; DeYoung, Lena L.A.; Gilbert, Anna C.; Jenkins, Gracie A.; Barthelemy, Christine M.; MacPherson, Heather A.; Radoeva, Petya D.; Kudinova, Anastacia Y.; Dickstein, Daniel P.
Highlights: While there is agreement that emotion dysregulation acts as a risk factor for harmful behaviors (e.g., suicide, non-suicidal self-injury[NSSI]), there is a lack of consensus about what features define it and how best to assess it. We looked at how different assessments of emotion dysregulation might differentiate mutually exclusive groups of adolescents: (1) those who have made a suicide attempt (SA), with no history of NSSI (SA-only); (2) those who have engaged in NSSI, with no history of an SA (NSSI-only); (3) community-recruited, typically developing controls without any form of psychopathology including NSSI or SA. Mean comparisons suggest that adolescents with a history of NSSI reported significantly lower distress tolerance and higher emotional reactivity when compared to adolescents who made an SA. After controlling for shared variance across emotion dysregulation measures, parent report of affective lability was the only scale to uniquely distinguish between NSSI and SA groups. Abstract: Emotion dysregulation is implicated in both suicide attempts (SA) and non-suicidal self-injury (NSSI). However, little is known about how emotion dysregulation may differ between adolescents who have made an SA from those engaged in NSSI. We sought to address this gap by comparing emotion dysregulation profiles across three homogenous groups of adolescents (1) SA-only (2) NSSI-only (3) and typically developing controls (TDCs). Mean comparisons suggest that adolescents with a history of NSSI reported significantly lower distress tolerance and higher emotional reactivity when compared to adolescents who made an SA. After controlling for shared variance across emotion dysregulation measures, parent report of affective lability was the only scale to uniquely distinguish between NSSI and SA groups. Accurately distinguishing emotion dysregulation patterns across self-injurious groups has practical implications towards assessment, treatment, course of illness, and prevention.